Cost-effectiveness analysis of nephroprotection programs for patients with type 2 diabetes mellitus in insurers in Colombia - Cristian Alejandro González-Rojas; Sergio Augusto Cáceres-Maldonado; Luis Alberto Soler-Vanoy; Lizbeth Alexandra Acuña-Merchán (Cost Effectiveness and Resource Allocation)
Abstract Background This research aimed to determine the cost-effectiveness of nephroprotection programs compared to no intervention in adults with type 2 diabetes mellitus (T2DM) in the Colombian national health system. Methods A Markov analysis with 3 disease states (controlled, uncontrolled and death) was modeled using a 1-year cycle and a 10-year time horizon based on T2DM and chronic kidney disease (CKD) data in Colombia from 2020 to 2023 from the perspective of the health insurance system. Effectiveness was considered as the control of CKD progression, with a decrease of estimated glomerular filtration rate (eGFR using CKD-EPI) of less than 5 ml/min/1.73 m2, and glycated hemoglobin (HBA1c) of less than or equal to 7%. Costs are expressed in 2023 $USD. Univariate and multivariate probabilistic sensitivity analyses were conducted using 1,000 Monte Carlo simulations. Results Compared to no intervention, nephroprotection programs were found to be cost-effective, with a dominant incremental cost-effectiveness ratio (ICER). Furthermore, the sensitivity analysis results showed that having a nephroprotection program is a cost-effective strategy in 89.2% and dominant in 56.7% of the simulations. Conclusions Nephroprotection programs result in better T2DM control and slower CKD progression, while also being lower in costs incurred during the year.